From Rejection to Accommodation: The Dynamics of Abu Bakar Ba'asyir's Ideological Shifts on Pancasila - Fanani, Zahrodin (Mafapress - Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA Pati, 2026)
The relationship between Islam and Pancasila remains a subject of ongoing debate within Islamic discourse in Indonesia, particularly when linked to the views of influential Islamic figures. Abu Bakar Ba’asyir is one such figure whose perspective on Pancasila has evolved over time rather than remaining static. This article aims to analyze the dynamics of Ba’asyir’s changing views on Pancasila through a textual analysis of his publicly available statements.This study employs a qualitative approach using textual analysis. The data consist of Abu Bakar Ba’asyir’s public statements, including transcribed speeches and documented written statements. The analysis is conducted chronologically to identify patterns, directions, and contextual factors underlying the shifts in his views across different periods.The findings indicate that Ba’asyir’s views on Pancasila have shifted in response to changing social, political, and legal contexts. These shifts demonstrate that the perspectives of Islamic figures on state ideology may evolve alongside broader societal dynamics. This study contributes to the discussion of Islamic political thought in Indonesia by highlighting the importance of analyzing public statements as a primary source for understanding ideological change.